PENYELESAIAN SENGKETA TUN TENTANG SK PEMBERHENTIAN PNS DI LINGKUNGAN PEMERINTAHAN PROVINSI DI TINJAU MENURUT UNDANG-UNDANG NOMOR 9 TAHUN 2004 TENTANG PERUBAHAN ATAS UNDANG -UNDANG NOMOR 5 TAHUN 1986 TENTANG PERADILAN TATA USAHA NEGARA - Pachreza Pachreza (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractCivil Servants (PNS) as the state apparatus has a very strategic position and a decisive role in organizing the government and development. As a state apparatus, civil servants are obliged to carry out government and development tasks with full loyalty and adherence to Pancasila, the 1945 Constitution, the state and government. Therefore, civil servants as implementers of legislation must endeavor to adhere to any laws and regulations in carrying out official duties.The authority of the judges of the State Administrative Court in resolving the civil service dispute In accordance with Law No.51 of 2009 on the State Administrative Court, it is stated that the judge of the court is an official performing the task of the judicial authority, in which the judicial authority's duties are in order to administer the judiciary and the judiciary itself has the obligation to examine, hear and decide a case. In short, a State Administrative Judge is an official authorized to examine, hear and decide a case within the State Administrative Court.